The Roxy letters - Lowry, Mary Pauline (Simon & Schuster, 2020)
"Meet Roxy. She's a sometimes vegan, always broke artist with a heart the size of Texas and an ex living in her spare bedroom. Her life is messy, but with the help of a few good friends and by the grace of the goddess Venus she'll discover that good sex, true love, and her life's purpose are all closer than she realizes. Bridget Jones penned a diary; Roxy writes letters. Specifically: she writes letters to her hapless, rent-avoidant ex-boyfriend--and current roommate--Everett. This charming and funny twenty-something is under-employed (and under-romanced), and she's decidedly fed up with the indignities she endures as a deli maid at Whole Foods (the original), and the dismaying speed at which her beloved Austin is becoming corporatized. When a new Lululemon pops up at the intersection of Sixth and Lamar where the old Waterloo Video used to be, Roxy can stay silent no longer. As her letters to Everett become less about overdue rent and more about the state of her life, Roxy realizes she's ready to be the heroine of her own story. She decides to team up with her two best friends to save Austin--and rescue Roxy's love life--in whatever way they can. But can this spunky, unforgettable millennial keep Austin weird, avoid arrest, and find romance--and even creative inspiration--in the process?"--Provided by publisher.